2016
DOI: 10.1902/jop.2016.160184
|View full text |Cite
|
Sign up to set email alerts
|

The Current Weight of Evidence of the Microbiologic Profile Associated With Peri‐Implantitis: A Systematic Review

Abstract: Results of this systematic review suggest moderate evidence supporting association of Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia and some evidence supporting association of Prevotella intermedia and Campylobacter rectus with the etiology of peri-implantitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
97
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 60 publications
(178 reference statements)
1
97
0
8
Order By: Relevance
“…S. sanguinis was recognized as a pioneer colonizer bacteria and its colonization can prepare favorable environment for later colonizers [15]. P. gingivalis, featuring predominantly anaerobic Gram-negative bacteria, was confirmed to have a high positive relationship with peri-implantitis [31]. Therefore, these two representative bacteria were chosen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…S. sanguinis was recognized as a pioneer colonizer bacteria and its colonization can prepare favorable environment for later colonizers [15]. P. gingivalis, featuring predominantly anaerobic Gram-negative bacteria, was confirmed to have a high positive relationship with peri-implantitis [31]. Therefore, these two representative bacteria were chosen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Currently lacking is clear consensus on what constitutes a true pathogenic biofilm in peri‐implantitis. Recent meta‐analysis concluded that the main bacterial species associated with peri‐implantitis are periodontal pathogens, most notably Pg 21 . Pg is unique among periodontal pathogens in that it is a “keystone pathogen,” causing dysbiosis or change in the microbial community that leads to destructive inflammation 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms formed were of low avidity and were easily removed by laser treatment (or water spray alone in case of smooth implant disk surfaces). Future studies are needed to develop a more clinically pertinent implant biofilm model, by coating disks with plasma/salivary binding proteins (e.g., fibronectin) to enhance bacterial binding 26 and using a mixed biofilm model 21 . Presence of residual bacteria in pits and fissures of rough titanium surfaces was noted, suggesting a need for testing a side firing tip or alternate wavelength to supplement the Er,Cr:YSGG laser.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown important differences. Likewise, the bacterial profile differences of healthy and diseased dental implants have also been studied 11,12 . Biofilm profiles of peri‐implantitis and healthy implants have shown controversial results.…”
mentioning
confidence: 99%
“…Two recent SRs on microbiologic profiles of peri‐implantitis have been published 11,12 . These reviews evaluated microbiologic profiles of peri‐implantitis compared with healthy implants, but not to periodontitis.…”
mentioning
confidence: 99%